KINERJA AGRIBISNIS MANGGA GEDONG GINCU DAN POTENSINYA SEBAGAI PRODUK EKSPOR PERTANIAN UNGGULAN (Forum Penelitian Agro Ekonomi, 2021)
Gedong gincu mango is a specific mango variety in West Java Province, which has a high economic value and the prospect of being a superior export commodity of Indonesia. Despite its increasing production and high market prospect, gedong gincu mango agribusiness still faces various problems, both in on-farm and off-farm aspects. This paper aims to study the agribusiness of gedong gincu mango, covering both on-farm and off-farm aspects and export prospects. In general, gedong gincu mango farmers are small-scale farmers who practice traditional cultivation, harvest, and post-harvest management; are not yet market-oriented, practicing conventional marketing that relies on collecting traders, and have weak institutional. These conditions cause low productivity and diverse quality of gedong mango and are not continuously available throughout the year, which hinders the potential for wide-open exports from being appropriately utilized. It needs improvement in both on-farm and off-farm to improve the production and marketing of gedong gincu mango. At the on-farm level, efforts to increase competitiveness can be made by improving fruit production, productivity, quality, and continuity, by applying good agricultural practices. At the off-farm level, this can be done by improving facilities and infrastructures, institutions, and regulations. These efforts should involve all parties, including farmers (producers), marketing agents (collectors, traders, exporters), and policymakers.